Religious Moderation from the Perspective of Maqashid al-Syariah: Islamic Education Strategies in Promoting Tolerance and Social Justice - Muhammadong, Muhammadong; Nurmila, Nurmila; Bando, Ushwa Dwi Masrurah Arifin; Utami, Farhah; Falihin, Dalilul (Journal of Legal and Cultural Analytics, 2025)
The purpose of this study is to analyze the application of religious moderation from the perspective of Maqashid al-Syariah and how Islamic education can play a role in promoting tolerance and social justice. This research employs a qualitative method with a literature review approach, examining various sources on religious moderation, Maqashid al-Syariah, and strategies in Islamic education. The findings indicate that religious moderation within the framework of Maqashid al-Syariah, which includes the protection of religion, life, intellect, lineage, and property, can serve as a foundation for designing Islamic education that prioritizes values of tolerance and justice. Islamic education based on Maqashid al-Syariah not only creates a generation that practices religion in a moderate way but also respects differences and applies principles of social justice in daily life. In conclusion, Islamic education that integrates Maqashid al-Syariah can be an effective strategy in building a harmonious, tolerant, and just society. Through education based on Maqashid al-Syariah, religious moderation can be realized, and the potential for social conflict caused by intolerance can be minimized, leading to peace and well-being for humanity.